La dramatización para el desarrollo de las competencias comunicativas en octavo grado, de la Unidad Educativa San Juan Bautista, periodo 2024-2025 - Medina Paccha, Kennelyn Carolina (2025)
The Curricular Integration Work named "Dramatization for the development of communicative competences in eighth grade, of the San JuanBautista Educational Unit, period 2024-2025", had as its general objective to determine the influence of the use of dramatization in the development of communicative competences of eighth grade students of the "San Juan Bautista" Fiscomisional Educational Unit. To do so, three specific objectives were proposed: the first, to identify the communicative competences that students have developed during their learning process; the second, to characterize the elements of dramatization to develop a pedagogical proposal that improves communicative competences in students; and the third, to develop a didactic proposal based on dramatization to improve the development of students' communicative competences. The research had a mixed approach, exploratory-descriptive, and used analytical, synthetic, deductive, inductive, statistical, and scientific methods. The techniques used included observation, diagnostic assessment and interviews, whose instruments were an observation sheet, a questionnaire and an interview guide. The sample consisted of thirty students and one teacher, selected by non-probabilistic sampling. The results show that the students have an average level in linguistic and sociolinguistic skills, and a low level in discursive, strategic and pragmatic skills. Therefore, elements of dramatization were characterized that support improving the identified difficulties, determining that dramatization positively influences the development of students' communicative skills, making it necessary for teachers to implement various strategies, including dramatization, taking advantage of the resources, modalities and benefits that it offers